Assessment of current patient reported outcome measures for three core outcome domains for single-sided deafness device intervention trials - Roulla Katiri; Deborah A. Hall; Derek J. Hoare; Sandra Smith; Bethany Adams; Kathryn Fackrell; Adele Horobin; Nicholas Hogan; Nóra Buggy; Pádraig T. Kitterick (Journal of Patient-Reported Outcomes)
Abstract Background Outcome reporting in clinical trials of auditory interventions for adults with Single-Sided Deafness (SSD) is inconsistent. The Core Rehabilitation Outcome Set for Single-Sided Deafness (CROSSSD) initiative has recommended three outcome domains as a minimum standard in the design of SSD intervention clinical trials. These are, Spatial orientation, Group conversations in noisy social situations, and Impact on social situations. The study objectives were to (i) understand exactly what the outcome domains mean to SSD experts, and (ii) identify and assess candidate PROMs in terms of how well they measure the experts’ conceptualisation of those SSD outcome domains. Methodology Stakeholder representatives participated in two semi-structured online focus groups. Participants were four adults diagnosed with SSD with experience of auditory interventions, two healthcare professionals working in the field, and one clinical researcher with experience in evaluating interventions. Thematic analysis was used to determine conceptual elements of each domain. COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) initiative recommendations were adopted to assess the relevance and comprehensiveness (content validity) of available candidate instruments. Results Multiple key concepts were identified for each outcome domain, and presented as a taxonomy. To be acceptable, any measurement instrument would need to achieve good coverage of all concepts in this taxonomy. From the 76 candidate instruments reviewed, none met accepted standards for content validity for SSD. The best performing candidates were (i) Spatial orientation: the Spatial Hearing Questionnaire and two variants of the Speech, Spatial and Qualities scale (SSQ-12, SSQ-18-C), (ii) Group conversations in noisy situations: the Communication Profile for Hearing Impaired (CPHI) questionnaire, SSQ-12, SSQ-18-C, and a multi-item questionnaire developed by Schafer and colleagues, and (iii) Impact on social situations: the CPHI questionnaire. Conclusions Multi-dimensional outcome domains introduce specific considerations for how they should be measured. Although some candidates instruments had reasonable comprehensiveness, modification is needed to ensure that there is overall greater relevance to the key concepts.